Peningkatan Database Pelanggan Untuk Usaha Depot Air Minum Isi Ulang (DAMIU) Berbasis Map Marker Di Wilayah Lamaru Kota Balikpapan - Ridhwan Haliq; Dian Mart Shoodiqin; Cut Keumala Banaget; Alfian Djafar; Faisal Manta (AMMA : Jurnal Pengabdian Masyarakat, 2025)
DAMIU is a microenterprise that has had significant growth in East Balikpapan, particularly in the Lamaru region. The necessity of water is paramount for humans, as it is a vital component of the body, supports essential activities, and is crucial for general health. Socialization occurs in person in the Lamaru Balikpapan Timur Health Center auditorium. Customers requiring water refills predominantly consist of stalls, private residences, and projects, with a general preference for delivery over self-collection at the depot. The distribution process employs a pick-up vehicle with a capacity of 60-70 gallons each trip. The survey results indicated a production of 3,800 liters per day for one vehicle. Among the 10 depots, 3 DAMIUs utilize one vehicle, while 7 DAMIUs employ 2 to 3 vehicles. The water supply utilized comprises 80% PDAM from 10 DAMIUs. Customers who are frequently disoriented and negligent impede the delivery procedure. Map Marker accurately identifies the client's location by interfacing with Google Maps and allows the input of images of residences, stalls, or locations, as well as customer telephone numbers. Participants from the socialization group rated it 6 out of 10, exhibiting complete curiosity about utilizing the application. DAMIU owners in the East Balikpapan area have achieved income stability and mitigated staff fraud through the utilization of the Map Marker application, presenting a significant advantage for them.